Toxicity of four kind plant extracts (Ageratum conyzoides L., Barringtonia asiatica (L.) Kurz., Melia azedarach L., Tephrosia vogelii Hook F.) against brown planthopper (Nilaparvata lugens STAL.) - Febritami, Giannisa; Usyati, N; Dono, Danar (CROPSAVER - Journal of Plant Protection, 2018)
One of the main pests that attack rice plants is the brown planthopper (BPH) or Nilaparvata lugens StÃ¥l. The negative impact of synthetic insecticides that have been used to control BPH causing increased desire to return to nature with the use of natural materials for plantÂ  protection. One source of natural ingredients that can be used in plant protection can come from plants as a botanical insecticide. Several plant species are known to have the botanical insecticidal activity such as Ageratum conyzoides (Asteraceae), Barringtonia asiatica (Lechytidaceae), Melia azedarach (Meliaceae) and Tephrosia vogelii (Fabaceae). In this research, toxicity testing was performed on extracs of A. conyzoides, B. asiatica, M. azedarach and T. vogelii to BPH, and its phytotoxicity on rice plants. The research was conducted using Completely Randomized Design (CRD) in experimental toxicity test of plant extract and phytotoxicity test on rice plant was done using 2 concentrations of 0.1% and 0.5% in each plant extract, and used 0.5% concentration on anti-oviposition effect. The results showed that T. vogelii methanol extract with 0,5% concentration caused the highest nymphs brown planthopper mortality which was 42,5% and at concentration 0,5% the four plant extract did not cause inhibition of oviposition activity on the BPH and did not cause phytotoxicity in rice plants.